2022
DOI: 10.3389/fncel.2022.980722
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-mediated neuroinflammation and neuroplasticity after stroke

Abstract: Stroke remains a major cause of long-term disability and mortality worldwide. The immune system plays an important role in determining the condition of the brain following stroke. As the resident innate immune cells of the central nervous system, microglia are the primary responders in a defense network covering the entire brain parenchyma, and exert various functions depending on dynamic communications with neurons, astrocytes, and other neighboring cells under both physiological or pathological conditions. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 225 publications
0
16
0
Order By: Relevance
“…Microglia play a central role in neuroinflammation through the release of multiple cytokines and chemokines 50 . Importantly, our findings indicated that Tregs may improve the injured spinal microenvironment through regulating microglia activation.…”
Section: Discussionmentioning
confidence: 65%
“…Microglia play a central role in neuroinflammation through the release of multiple cytokines and chemokines 50 . Importantly, our findings indicated that Tregs may improve the injured spinal microenvironment through regulating microglia activation.…”
Section: Discussionmentioning
confidence: 65%
“…M1 activation, known as the classically activated phenotype, is induced by lipopolysaccharide (LPS), granulocyte-macrophage colony-stimulating factor (GM-CSF), and interferon-γ (IFN-γ), and is thought to be a pro-inflammatory and neurotoxic state. It is characterized by the secretion of pro-inflammatory cytokines and chemokines such as interleukin (IL)-1β, IL-6, IL-12, and tumor necrosis factor-α (TNF-α) as well as the production of neurotoxic substances, including ROS, inducible nitric oxide synthase (iNOS), and proteolytic enzymes including matrix metalloproteinase (MMP)3 and MMP9 [ 9 , 86 , 87 , 88 ]. Double-negative T cells (DNTs) have been found to secrete large amounts of TNF-α, promoting the activation of NOD-like receptor thermal protein domain associated protein 3 (NLRP3) and inducing microglia pro-inflammatory polarization [ 89 ].…”
Section: Activation and Polarization Of Microglia Following Strokementioning
confidence: 99%
“…M2 activation, also known as alternatively activated, is induced by IL-4, IL-13, and IL-10 to secrete anti-inflammatory cytokines, such as IL-10 and transforming growth factor-β (TGF-β). They also release growth factors such as insulin-like growth factor-1 (IGF-1), colony-stimulating factor-1 (CSF-1), vascular endothelial growth factor (VEGF), and neurotrophins such as brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF), and their markers such as arginase-1 (Arg-1), chitinase-like protein 3 (also known as Ym1), cluster of differentiation (CD)163, and CD206, which are involved in tissue regeneration and repair, removal of cell debris, provision of trophic factors, and preservation of tissue dynamics following infection or damage [ 9 , 75 , 86 , 87 , 91 , 92 ]. The M2 phenotype can be further divided into three subclasses: M2a, M2b, and M2c [ 93 ].…”
Section: Activation and Polarization Of Microglia Following Strokementioning
confidence: 99%
See 2 more Smart Citations